Genomic Sequencing of Japanese Plum (Prunus salicina Lindl.) Mutants Provides a New Model for Rosaceae Fruit Ripening Studies - Fernandez i Marti, Angel; Saski, Christopher A.; Manganaris, George A.; Gasic, Ksenija; Crisosto, Carlos H. (Frontiers in Plant Science, 2018)
It has recently been described that the Japanese plum ‘Santa Rosa’ bud sport series contains variations in ripening pattern: climacteric, suppressed-climacteric and non-climacteric types. This provides an interesting model to study the role of ethylene and other key mechanisms governing fruit ripening, softening and senescence. The aim of the current study was to investigate such differences at the genomic level, using this series of plum bud sports, with special reference to genes involved in ethylene biosynthesis, signal transduction, and sugar metabolism. Genomic DNA, isolated from leaf samples of six Japanese plum cultivars (‘Santa Rosa’, ‘July Santa Rosa’, ‘Late Santa Rosa’, ‘Sweet Miriam’, ‘Roysum’, and ‘Casselman’), was used to construct paired-end standard Illumina libraries. Sequences were aligned to the Prunus persica genome, and genomic variations (SNPs, INDELS, and CNV’s) were investigated. Results determined twelve potential candidate genes with significant copy number variation, being associated with ethylene perception and signal transduction components. Additionally, the Maximum Likelihood (ML) phylogenetic tree showed two sorbitol dehydrogenase genes grouping into a distinct clade, indicating that this natural group is well-defined and presents high sequence identity among its members. In contrast, the ethylene group, which includes ACO1, ACS1, ACS4, ACS5, CTR1, ERF1, ERF3 and ethylene-receptor genes, was widely distributed and clustered into ten different groups. Thus, ACS, ERF and sorbitol dehydrogenase proteins potentially share a common ancestor for different plant genomes, while the expansion rate may be related to ancestral expansion rather than species-specific events. Based on the distribution of the clades, we suggest that gene function diversification for the ripening pathway occurred prior to family extension. We herein report all the frameshift mutations in genes involved in sugar transport and ethylene biosynthesis detected as well as the gene copy number variation implicated in ripening differences.